1998
DOI: 10.1093/intimm/10.9.1289
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of the MHC class I-related receptor, FcRn, in endothelial cells of mice

Abstract: Our recent data indicate that the MHC class I-related receptor, FcRn, plays a role in regulating serum IgG levels, in addition to its known role in transferring IgG from mother to young. In the current study, the distribution of FcRn in adult mice has been investigated using several approaches. First, tissue distribution of anti-FcRn F(ab')2, murine IgG1 and recombinant, IgG1-derived Fc-hinge fragments has been analyzed, and these FcRn binding proteins localize predominantly in skin and muscle with lesser amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
189
5
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(221 citation statements)
references
References 31 publications
22
189
5
1
Order By: Relevance
“…Because the vascular endothelium of skin and skeletal muscle are proposed to be the sites at which FcRn protects serum IgG from degradation, we first examined these tissues (15). Consistent with previous reports, we found that FcRn was expressed at high levels in the vasculature of these organs (Fig.…”
Section: Fcrn Expression In the Skin And Skeletal Musclesupporting
confidence: 80%
See 3 more Smart Citations
“…Because the vascular endothelium of skin and skeletal muscle are proposed to be the sites at which FcRn protects serum IgG from degradation, we first examined these tissues (15). Consistent with previous reports, we found that FcRn was expressed at high levels in the vasculature of these organs (Fig.…”
Section: Fcrn Expression In the Skin And Skeletal Musclesupporting
confidence: 80%
“…To protect serum IgG from catabolism, FcRn is predicted to function at sites that have a large contact area with the blood such as the vascular endothelium of the skin and skeletal muscle (15). In fact, FcRn has been shown to be highly expressed in a variety of different endothelial beds.…”
Section: Neonatal Fcr Expression In Bone Marrowmentioning
confidence: 99%
See 2 more Smart Citations
“…The full model (Fig. 1A) features a functional catabolic and recycling site within the vascular compartment consisting of endosome-rich endothelium [24] into which plasma IgG is constitutively pinocytosed by a fluid-phase endocytic process at a fractional uptake rate (k up ), which is FcRn-independent since FcRn binding takes place after acidic sorting endosomes are formed [25], unlike cell-surface receptor-mediated uptake of LDL or transferrin. While pinocytosis/exocytosis is potentially bidirectional, k up is a fractional rate of "net" movement (thus smaller in magnitude than the 'real' unidirectional uptake rate) from the plasma into the sorting endosomes where IgG binds FcRn according to its binding affinity (equilibrium binding constant; K D ) in an acidic endosomal environment [25].…”
Section: The Integrated Kinetic Modelmentioning
confidence: 99%